Seedlings of Cedrela fissilis Vell. respond to single superphosphate application, but not to liming - Menezes Franco, Tayssa; Lima de Souza, Juciley; Darlon Nascimento Alves, José; Costa Esteves Junior, Fabio; Neves de Oliveira, Jairo; de Oliveira Ferreira, Eric Victor (Revista Ceres, 2023)
Cedro-rosa (Cedrela fissilis) is native to Brazil with great potential for seedling production. However, soil correction is necessary to improve its performance, due to the edaphoclimatic conditions in Brazil, where soils have a high weathering degree and large amounts of Fe and Al oxides. Here, we evaluated the combined effect of soil acidity correction by liming and phosphate fertilization using single superphosphate on the growth and development of cedro-rosa seedlings cultivated in Amazonian soil. The study was carried out in a greenhouse at the Universidade Federal Rural da Amazônia (UFRA) – Campus Capitão Poço, between July and December 2019. Different levels of base saturation (V%) showed no influence on the variables analyzed. On the other hand, phosphorus (P), calcium (Ca), and sulfur (S) supplied by single superphosphate significantly influenced growth and development of cedro-rosa seedlings. The optimum P levels for stem diameter (SD), leaves number (LN), root dry matter (RDM), stem dry matter (StDM), leaf dry matter (LDM), total dry matter (TDM) were 405, 286, 385, 421.87, 393.75, 445 mg dm-3 of P, respectively. Seedling quality (DQI) showed a positive linear response to levels of P, Ca, and S in single superphosphate. Thus, fertilization with P was necessary at the nursery stage for the cultivation of the species in soil of low chemical fertility. For better quality of cedro-rosa seedlings grown in pots, the application of 400 mg dm-3 of P is recommended.